Pengaruh Persepsi Harga Dan Citra Merek Terhadap Kepuasan Penumpang Di Maskapai Batik Air Pada Bandar Udara Ahmad Yani Semarang - Muhamad Ananda Rafisya; Dhiani Dyahjatmayanti (Lembaga Pengembangan Kinerja Dosen, 2023)
Every company is required to make customers feel satisfied by providing better offers and services, considering that companies must be able to maintain their market position in the midst of increasingly fierce competition. To win the competition, companies must be able to provide satisfaction to customers, one example is a transportation service company. The objectives of this study include: Knowing the effect of price perceptions on passenger satisfaction at Batik Air Airlines at Ahmad Yani Airport in Semarang, knowing the effect of brand image on passenger satisfaction at Batik Air Airlines at Ahmad Yani Airport Semarang, and knowing the influence of price perceptions and brand image as a whole. along with passenger satisfaction at Batik Air at Ahmad Yani Airport in Semarang. This research methodology is a quantitative research using a questionnaire method. The population of this study are passengers who use the services of Ahmad Yani Airport in Semarang. researchers took data from a sample of 100 respondents, the sampling technique to be used is probability sampling. The type of sampling technique in this study used purposive sampling. Data collection tools include: questionnaires and documentation. Source of data used primary data and secondary data. Data analysis technique used: multiple linear regression includes the T test, F test and the coefficient of determination. The sig value of the price perception variable (X1) is 0.946 which can be concluded that 0.946 > 0.05 so that H1 is rejected, and the sig value of the brand image variable (X2) is 0.000 which can be concluded that 0.000 <0.05 so that H2 is declared accepted, which means that there is the effect of the results obtained by the researchers which resulted that price perceptions had no effect on passenger satisfaction and brand image had an effect on passenger satisfaction was obtained from the SPSS results carried out by researchers. And a Sig value of 0.000, it can be concluded that a sig value of 0.000 <0.05 means that there is an influence of perceived price and brand image simultaneously on passenger satisfaction.